Does dietary intake change during an intervention to reduce sedentary behavior and cardiovascular disease risk? A randomized comparative effectiveness trial - Casey, Kelsey; Mailey, Emily L.; Rosenkranz, Sara K.; Rosenkranz, Richard R.; Swank, Aaron; Ablah, Elizabeth (My University, 2018)
Background: Evidence from physical activity interventions suggests that women, in particular, may overcompensate for exercise energy expenditure by increasing caloric intake. Sedentary behavior and poor dietary quality are independent risk factors for many major chronic diseases, including cardiovascular disease (CVD). The primary purpose of this study was to determine whether insufficiently active women, accumulating less than 60 min per week of moderate-to-vigorous physical activity, alter caloric intake or dietary quality when participating in an 8-week intervention to reduce sedentary behavior and CVD risk. A secondary aim was to determine whether the two treatment groups differed from one another in dietary intake while participating in the intervention. Methods: Insufficiently active women (n = 49) working full-time sedentary jobs were randomized to one of two treatment groups to reduce sedentary behavior during the workweek: short-break (1–2 min breaks from sitting every half hour, SB), or long-break (15 min breaks from sitting twice daily, LB). Three-day food records were collected at baseline, week 4 and week 8. Dietary quality was assessed using the Alternative Healthy Eating Index 2010 (AHEI-2010). Risk factors for CVD were assessed at baseline and week 8. Results: For all participants, average caloric intake decreased significantly from baseline to week 8 by approximately 12% (Δ = − 216.0 kcals, p = 0.003). Average caloric intake decreased significantly over time for the SB group (Δ = − 369.6 kcals, p = 0.004), but not the LB group (Δ = − 179.5 kcals, p = 0.17). There was no significant difference between SB and LB groups with regard to calories from baseline to week 8 (F = 0.51, p = 0.48). Total AHEI-2010 scores did not decrease significantly for all participants (Δ = − 4.0, p = 0.14), SB (Δ = − 5.2, p = 0.16), or LB groups (Δ = − 4.5, p = 0.67). Conclusions: Following an 8-week intervention to reduce sedentary time, insufficiently active women decreased caloric intake over time, however there were no differences between SB and LB groups. In all participants, dietary quality was not altered over time. Future studies should explore sedentary reduction interventions compared to physical activity interventions as a means to create negative energy balance, as frequent sedentary breaks may be effective for improving health outcomes in women. Trial registration: ClinicalTrials.gov registration number NCT02609438, retrospectively registered November 20, 2015.
Citation: Casey, K., Mailey, E. L., Rosenkranz, R. R., Swank, A., Ablah, E., & Rosenkranz, S. K. (2018). Does dietary intake change during an intervention to reduce sedentary behavior and cardiovascular disease risk? A randomized comparative effectiveness trial. BMC Nutrition, 4(1). https://doi.org/10.1186/s40795-018-0223-1
Keywords: Sedentary; Insufficiently active women; Alternative healthy eating index; Dietary change; Dietary quality; Cardiovascular disease risk